Synergistic interaction among reservoirs along a cascade system and their response to the ongoing anthropogenic and climatic pressures: evidence from deterministic hydrodynamic-biogeochemical modelling - Soares, Laura Melo Vieira (2021)
Reservoirs have been constructed in sequence along large rivers worlwide, forming cascade systems of interconnected aquatic environments. The general understanding of the physic and biogeochemical processes in lentic environments has improved over the last several decades, however, solid evidence of potential interactions among reservoirs along a cascade system remains unclear. Therefore, the main objectives of the present thesis were to comprehend the complexity of interconnected aquatic ecosystems and their response to the ongoing anthropogenic and climatic pressures faced by six reservoirs along the Tietê River (Southeast Brazil). There is a great interest in the water quality of these reservoirs in face of their multiple uses. The deterministic General Lake Model coupled to the Aquatic EcoDynamics (GLM-AED) was applied to simulate the major internal processes affecting water quality within the reservoirs. The present thesis introduced two novel model approaches: (i) a parameterization strategy was applied to accomplish a better estimation of potential sensitive parameters to overcome the challenge of exploring hydrodynamics in two reservoirs with a lack of measured temperatures; and (ii) a sequential modelling approach that fully links reservoirs\' processes, in which alterations in the boundary conditions is propagated through one water body to the next. The model was then applied to (1) demonstrate the effects of climate change on the hydrodynamics of the uppermost reservoir in the system over 26 years (1993–2018). Results have indicated that the reservoir has experienced significant warming since 1993 related to increasing air temperature and decreasing wind speed; (2) prove a synergistic interaction among reservoirs triggering a domino effect along the cascade system, thus affecting the water quality further downstream. Results revealed that a reduction in phosphorus loads into the uppermost reservoir resulted in higher reduction rates in the downstream ones, revealing their capacity to act as a sink of phosphorus; and (3) test scenarios of classical restoration methods to provide guidance on optimised restoration efforts at a basin catchment scale. Results showed that a combination of on-land and in-lake restoration techniques devoted to the uppermost reservoir would promote restoration from eutrophication not only in the reservoir itself, but in all downstream ones along the cascade system. The present findings are of great scientific interest as they provide a deep understanding of the physical limnology of subtropical reservoirs, where information is still limited. Also, they may be of primary interest to water managers as it allows the identification of the most strategic reservoir to devote management actions for establishing an efficient restoration program at a catchment scale and ensure water security for future generations.